PREPARATION AND EVALUATION OF DOLUTEGRAVIR SOLID DISPERSIONS - MUPPARAJU, SUNDEEP; SURYADEVARA, VIDYADHARA; DOPPALAPUDI, SANDEEP (International Journal of Applied Pharmaceutics, 2021)
Objective: The current work mainly focuses on solubility enhancement of dolutegravir which is a BCS (Biopharmaceutical Classification System) class-II drug using various excipients. Methods: Solid dispersions of dolutegravir were prepared by solvent evaporation and fusion methods using carriers like poloxamer-188 and plasdone K-29/32 in different ratios (1:0.5 to 1:3.0). The amount of dolutegravir used was kept constant and the polymer concentrations were increased. Various physical parameters like angle of repose, carr’s index, Hausner’s ratio were calculated for the prepared solid dispersions. They were also evaluated for particle size and drug content uniformity along with in vitro drug release. Characterization studies like Fourier Transform Infra-Red spectroscopy (FTIR), Differential Scanning Calorimetry (DSC), Scanning Electron Microscopy (SEM) and X-Ray Diffraction (XRD) were also done. Results: Dolutegravir solid dispersions showed good to excellent flow properties. From in vitro dissolution studies, it was observed that the solid dispersion formulation DF3 containing dolutegravir and poloxamer-188 in 1:1.5 ratios prepared by fusion method showed better dissolution rate when compared with other formulations. The dissolution parameters were also evaluated. DF3 showed a higher drug release of 86.33% in 60 min. FTIR and DSC studies revealed that there were no major interactions between drug and excipients. XRD studies revealed the nature of formulations. Conclusion: The solid dispersions prepared using poloxamer-188 by fusion method has enhanced the solubility of dolutegravir.